2023
DOI: 10.3390/su15064981
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Heterogeneity among Youth: A Missing Link in Enhancing Youth Participation in Agriculture—A South African Case Study

Abstract: Youth participation in the agricultural sector remains key to addressing youth unemployment. Young people represent a heterogeneous social group with markedly diverse social and economic needs that require tailor-made support interventions to enhance their participation in agricultural activities. The main objective of this article was to develop distinct youth typologies informed by diverse endowment of livelihood assets, including the psychological assets and entrepreneurial characteristics that shape young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Therefore, based on the classification proposed by DFID, the paper constructed an assessment index system of rural household livelihood sustainability from five dimensions of livelihood capital, including human, natural, physical, financial, and social capital. Then, considering the existing references [35][36][37][38][39][40] on indicators related to livelihood capital and the availability of data in the study area, 17 representative indicators of the criteria layer were identified (Table 1). More details about the references and category assignment of each index are given in Appendix A (Table A1).…”
Section: Livelihood Sustainability Evaluation Indicator Systemmentioning
confidence: 99%
“…Therefore, based on the classification proposed by DFID, the paper constructed an assessment index system of rural household livelihood sustainability from five dimensions of livelihood capital, including human, natural, physical, financial, and social capital. Then, considering the existing references [35][36][37][38][39][40] on indicators related to livelihood capital and the availability of data in the study area, 17 representative indicators of the criteria layer were identified (Table 1). More details about the references and category assignment of each index are given in Appendix A (Table A1).…”
Section: Livelihood Sustainability Evaluation Indicator Systemmentioning
confidence: 99%
“…Despite these benefits, training/capacity building efforts should not be blanket for all engagement with young people, even for the same technical area or geographical location, but should be contextualized to the specific young people that one is dealing with. This is because young people in agriculture are not a homogeneous group but differ due to numerous factors (Maïga et al 2020;Geza et al 2021;Madende et al 2023).…”
Section: Benefits For Young People and Women As Service Providersmentioning
confidence: 99%
“…Four typologies developed by Madende et al (2023) were selected for the purpose of creating development pathways that are tailor-made for selected youth typologies. The selected typologies are, (1) job secure, (2) gender sensitive with negative PsyCap, (3) social grant reliant households and (4) resource-poor traditional livestock farmers.…”
Section: Datamentioning
confidence: 99%
“…Development pathways developed for specific typologies of people have been considered key to guiding interventions to achieve specific development outcomes in agriculture (Chipfupa and Tagwi 2021;Madende et al 2023). Typologies have been applied in the literature to guide and coordinate specific interventions within development pathways, for a specific group, to achieve a given outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation